First Report of NDM-1-Producing Acinetobacter baumannii Sequence Type 25 in Brazil - Pillonetto, Marcelo (2014)
Pontifical Catholic University.School of Health and Biosciences. Curitiba, PR, Brasil / State Central Public Health Laboratory. São José dos Pinhais, PR, Brasil.